2016
DOI: 10.1053/j.gastro.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Relamorelin Reduces Vomiting Frequency and Severity and Accelerates Gastric Emptying in Adults With Diabetic Gastroparesis

Abstract: In a clinical trial of patients with diabetic gastroparesis, relamorelin (10 μg twice daily) significantly accelerated gastric emptying and significantly reduced vomiting, compared with placebo. Among patients with baseline vomiting, relamorelin had prokinetic effects and significantly reduced vomiting and also improved other symptoms of diabetic gastroparesis compared with placebo. ClincialTrials.gov number: NCT01571297.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 22 publications
0
93
0
6
Order By: Relevance
“…This effect was quantified by the decrease in GEBT T½, with results similar to findings evident after 4 weeks of relamorelin treatment in a prior diabetic gastroparesis clinical trial. 21 The difference of >10% over placebo needs to be considered in relation to the relatively low calorie content of the test meal (230 kcal). The robust effects of relamorelin on some diabetic gastroparesis symptoms (particularly nausea, postprandial fullness, bloating and abdominal pain) are consistent with the prokinetic action of relamorelin on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect was quantified by the decrease in GEBT T½, with results similar to findings evident after 4 weeks of relamorelin treatment in a prior diabetic gastroparesis clinical trial. 21 The difference of >10% over placebo needs to be considered in relation to the relatively low calorie content of the test meal (230 kcal). The robust effects of relamorelin on some diabetic gastroparesis symptoms (particularly nausea, postprandial fullness, bloating and abdominal pain) are consistent with the prokinetic action of relamorelin on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in humans have shown a terminal half-life of ~4.5 hours, though, at highest doses, the terminal half-life was 19.4 hours. 21 Toxicologic studies with relamorelin provide >750-fold safety margins compared with dose exposures reported in clinical trials. In prior pharmacokinetic studies, it was estimated that only 8% of relamorelin is excreted in urine, and pharmacokinetics of relamorelin appears similar in healthy volunteers and patients with diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relamorelin is a novel long acting ghrelin agonist with 15–130 fold greater potency than the natural peptide that increases antral contractions in healthy controls and accelerates gastric emptying in type 1 and type 2 diabetics with gastroparesis (91, 92, 93, 94). In a multicenter, 4 week phase 2A trial in 204 diabetics with gastroparesis, relamorelin therapy produced greater gastric emptying acceleration versus placebo with associated decreases in vomiting severity and frequency (95). In 119 patients with baseline reports of vomiting from this study, relamorelin significantly reduced nausea, vomiting, abdominal pain, bloating, and early satiety versus placebo.…”
Section: Medications Used To Treat Nausea and Vomitingmentioning
confidence: 99%